Магнетно-резонантна холангиопанкреатографија радиолошки метод во дијагностиката на болестите на панкреато-билијарниот систем - Пргова, Билјана (Медицински факултет, УКИМ, Скопје, 2015)
The purpose of this study is to determine the value of the Magnetic Resonance Cholangiopancreatography(MRCP) which is a special imaging method that allows visualisation of intra and extrahepatic gall ducts as well as the pancreatic duct. This method was introduced in 1981, for the first time, and since then, it has been permanently being developed as a technique and a method of examination, and its diagnostic value has been confirmed. Today, MRCP is comparable with endoscopic retrograde holangiography which is a well established method or a golden standard for examination of billiar-pancreatic pathology. This study included a representative pattern of 120 patients of both genders,at the age from 30 to 70. We examined the diagnostic value of the method in an evaluation of billiar obstruction, etiology of the billiar obstruction, anatomic abnormalities and holedoholitiasis. The golden standard were the endoscopic retrograde holangiography, computerised tomography and pathohistologicals findings. The advantages of the magnetic resonance cholangiopancreatography are: it is not invasive; it is cheaper with pictures that have the same quality as those obtained with the use of endoscopic retrograde holangiography; no contrast is used; there is no X-ray treatment; there are no complications. Downside : It has only diagnostic, but not therapeutic opportunity. MRCP is based on T2 pulse sequence from the FSE (fast spin echo) family when the contents of the billiar-pancreatic trunk is with a hypersignal while the parenchimal organs are with a hyposignal. The combination of signals provides a good contrast and makes the diagnosis of the billiar-pancreatic system easy. Conclusion: Patients prefer MRCP as a diagnostic method. MRCP is a complete diagnostic evaluation. It is an irreplaceable diagnostic method for the patients for whom ERCP can not be realized. When combined with MR(magnetic resonance) on the abdomen, it is a method which is superior in determination of malignant diseases staging.
Докторска дисертација одбранета во 2015 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Билјана Таушанова.
Keywords: ERCP, MRCP, pathology of pancreatobilliar system